Prevalence of tick species in sheep and goat flocks in areas of southern Greece - DIMANOPOULOU, A. P.; STARRAS, A. G.; DIAKOU, A.; LEFKADITIS, M.; GIADINIS, N. D. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of this study was to investigate the tick prevalence and to identify the species of ticks that parasitise the small ruminant flocks in the prefectures of Achaia (in the geographic region of Peloponnese) and Chania (in the island of Crete). Thirty flocks of goats and sheep were examined for tick parasitism during the period from December 2012 until August 2013. Sixteen of them were in Achaia and the rest 14 in Chania. In total, 84 goats and 148 sheep were examined; from them, 50 goats and 70 sheep in Achaia, and 34 goats and 78 sheep in Chania. The species Dermacentor marginatus was identified in Achaia in 15% of the animals. In Chania the species identified were Haemaphysalis punctata (13%), Hyalomma anatolicum (4.47%), Rhipicephalus sanguineus (4.47%) and Ixodes ricinus (3.58%). This is the first study on tick infestation in sheep and goats in Peloponnese and Crete, two areas with large number of small ruminant population and important tradition in small ruminant farming.